The Risk of Postoperative Hemorrhage and Efficacy of Heparin for Preventing Deep Vein Thrombosis and Pulmonary Embolism in Adult Patients Undergoing Neurosurgery: A Systematic Review and Meta-Analysis. (December 2017) - Wang, Xuan; Zhou, Ying-Chun; Zhu, Wen-De; Sun, Yun; Fu, Peng; Lei, De-Qiang; Zhao, Hong-Yang
The aim of this meta-analysis was to examine the risk of postoperative bleeding and efficacy of heparin for preventing deep vein thrombosis (DVT) and pulmonary embolism (PE) in adult patients undergoing neurosurgery. MEDLINE, Cochrane, and EMBASE databases were searched until October 31, 2016, for randomized controlled trials (RCTs) and non-randomized comparative studies that assessed the rates of postoperative hemorrhage, DVT, PE, and mortality in adult patients undergoing neurosurgery. Nine eligible studies (five RCTs, four retrospective studies) including 874 patients treated with either unfractionated heparin (UFH) or low-molecular-weight heparin (LMWH) and 1033 patients in control group (placebo with or without compression device) were analyzed. The overall analysis revealed that there was an increase in the risk of postoperative hemorrhage in patients who received heparin (pooled OR 1.66, 95% CI 1.01 to 2.72, p=0.046) compared with no treatment group. The risk of postoperative hemorrhage was more significant if only RCTs were included in analysis. Heparin prophylaxis was associated with a decrease in the risk of DVT (pooled OR 0.48, 95% CI 0.36 to 0.65, p<0.001) and PE (pooled OR 0.25, 95% CI 0.09 to 0.73, p=0.011) but it did not affect the rate of mortality. In conclusion, heparin increased the rate of postoperative bleeding, decreased the risk of DVT, PE and venous thromboembolic event (VTE) but it did not affect the mortality of patients undergoing neurosurgery. For the heparin prophylaxis, the trade-off between the risk of postoperative bleeding and benefit of prophylaxis against VTEs requires further investigation.